Vulnerable responsibility Small vices for caregivers - Burggraeve, Roger (UJ Press, 2018)
The authors have developed the ethical imagination inviting a sense of "otherness" towards the vulnerable self, rebounding care for the other as a way to understand our everyday neurotic (normal) tendency of small vices as the propensity and possibility for responsibility towards the other. The authors, inviting the reader into troublesome feelings such as laziness and anger, bring a Levinasian horizon into focus, so that even in the midst of laziness, there remains the small goodness to set the self free to care for the other, meeting the demands, challenges, hesitation, shuddering, tension and shocks of such alterity, of living "otherwise".